Family Meal Environment Differentially Conditions the Prospective Association between Early Childhood Screen Time and Key Social Relationships in Adolescent Girls - Kianoush Harandian; Beatrice Necsa; Tracie A. Barnett; Linda S. Pagani (MDPI AG, 2024)
Background: Despite screen time recommendations, children are increasingly spending time on electronic devices, rendering it an important risk factor for subsequent social and developmental outcomes. Sharing meals could offer a way to promote psychosocial development. This study examines the interaction between family meal environment and early childhood screen time on key adolescent social relationships. Methods: Participants are 1455 millennial children (49% boys) from the Quebec Longitudinal Study of Child Development birth cohort. Parents reported on child screen use at ages 2 and 6 years and family meal environment quality at age 6 years. Parents and children reported on parent-child relationships and peer victimization experiences, respectively, at age 13 years. Sex-stratified multiple regression estimated the direct association between screen time trends, family meal environment quality, and their interaction on later social relationship outcomes. Results: For girls, when preschool screen time increased, sharing family meals in high-quality environments was associated with more positive and less conflictual relationships with their mothers, whereas meals shared in low- and moderate-quality environments were associated with fewer instances of victimization by their peers. Non-linear associations were not significant for boys. Conclusion: Capitalizing on family meal environment represents a simple/cost-efficient activity that can compensate for some long-term risks associated with increased screen use, above and beyond pre-existing and concurrent individual and family characteristics. Public health initiatives may benefit from considering family meals as a complementary intervention strategy to screen use guidelines.